In Memoriam: Prof. Valerii Viktorovych Vit (Ukrainian Journal of Ophthalmology, 2023)
The legendary professor Valerii Viktorovych Vit passed away on April 22, 2023.He was born in Odesa in 1948.After graduating from the Faculty of General Medicine, Odesa Medical Institute, in 1972, Vit worked some time as a dissector at Odesa Regional Hospital.He began his science career at the Filatov Institute of Eye Diseases and Tissue Therapy in 1975 as a junior research associate at the Pathomorphology Laboratory, became head of the laboratory in 1978 and was promoted to the Deputy Director for Science at the institute in 1991.Valerii Viktorovych Vit defended his Cand Sc (Med) thesis in 1978, and doctoral (Dr Sc (Med)) dissertation, The Pathological Anatomy and Therapeutic Pathomorphosis of Human Pigmented Uveal Tumors, in 1986. The dissertation research was conducted under Professor V.V. Voino-Yasenetskyi, an outstanding scientist, and focused on the morphogenesis and malignancy of human choroidal and ciliary tumors. Valerii Viktorovych Vit was promoted to professorship in 1989.He authored or co-authored about 400 papers and five monographs on visual system structure and the pathological anatomy of eye disease. Five individuals completed their Dr Sc (Med) degrees, and 18, their Cand Sc (Med) degrees, under the supervision or mentorship of Prof. Vit.He was the first to raise questions on the value of ocular oncology studies on (a) the transformation of an eye tumor in the course of treatment and (b) the efficacy of the therapy used for treatment.He will be remembered as an exceptionally talented doctor, scientist and manager of high competence and great professional experience and a person with a strong commitment to work.By his pupils and colleagues, Professor Vit, a true professional in his field, will remain a cherished memory. We offer our condolences to his family and loved ones.